(untitled) - Stickney, Clyde P. (Orlando, Florida, 1997)
The book presents a general overview of the principal financial statements; discusses the basic accounting model accountants use to generate the principal financial statements. It considers the specific accounting priciples or methods used in preparing the financial statements. Finally, The book combines effects of alternative accounting methods on the financial statements. The end of the book includes a comprehensive glossary of accounting terms
Keywords: Corporations,Financial management,Financial statements,Managerial accounting; Accounting